Pomen spanca pri športnikih - Hadžić, Alen (Šport (Ljubljana), 2017)
Sleep is a physiological process that may be fundamental for human health. Acute and chronic sleep deprivation is a big problem of modern society in all categories, as no one is immune to this and we may fact the same problem in children, adolescents, adults, and elderly and of course trained athletes. Sleep deprivation in athletes has important consequences in the terms of physical and cognitive abilities, and leads to inadequate recovery after exercise increasing the risk of overtraining syndrome. This paper has outlined the reports from several review papers in order to improve the awareness of sport professionals about the importance of sleep for athletes.
Keywords: active rest; aktiven počitek; athletes; okrevanje; overtraining; počitek; pomen; pretreniranost; recovery; regeneracija; regeneration; sleep; spanec; sport; šport; športniki; verreaching